Adaptive Leadership Strategies in PKBM: Integrating Educator Involvement and Communication for Sustainable Community Partnerships - Hendry Hermawan; Ahmad Suriansyah; Sulistiyana Sulistiyana; Aslamiah Aslamiah (Edunesia : Jurnal Ilmiah Pendidikan, 2026)
This study examines leadership strategies used by PKBM heads to build sustainable community partnerships, with attention to educator involvement and communication. Using a qualitative multi-site design, the research was conducted at PKBM Merah Putih and PKBM Azka Bamega in Kotabaru Regency, involving two heads, ten educators, and six community partners. Data were gathered through interviews, observation, and documentation, then analyzed inductively with Miles and Huberman’s (2014) interactive model and triangulation. Findings indicate that PKBM Merah Putih used participatory leadership, engaging educators in evaluations and collaborative decisions, whereas PKBM Azka Bamega relied on centralized leadership, strong in external partnerships but limited in educator participation. Communication combined coordination meetings, local collaboration, and contextual approaches. Cross-site synthesis revealed an adaptive integrative model balancing internal collaboration and external coordination. The study offers a context-responsive framework for non-formal education governance and practical guidance for strengthening educator capacity, communication, and sustainable partnerships in similar community-based settings nationwide.